The polychaete Magelona filiformis n.sp. and notes on other species of Magelona - Wilson, Douglas P. (Journal of the Marine Biological Association of the United Kingdom, 1959)
None. Begins: As already mentioned (Wilson, 1958), a species of Magelona from clean sand near low water at Mill Bay, Salcombe, has not yet been described. This worm was first noticed in 1939; it is recorded in the 1957 edition of the Plymouth Marine Fauna as ‘Magelona sp.’ and it is there mentioned that artificial fertilizations were made and larvae reared in April-September 1939, and that these larvae differed from those of the other two Magelona species from the Plymouth district (papillicornis F. Müller and alleni Wilson). The worm is still common in the same locality at Salcombe, in the same ground and often in the same spade-full as papillicornis, but it is not as abundant as the latter and probably not as abundant as it was when first seen in 1939. A very good low tide receding below datum is needed to collect it; it is easily overlooked on account of its fragility and fine thread-like appearance, mature females coloured pink by their contained eggs being more readily seen while digging than translucent immature worms or white males. Worms are difficult to collect whole, the tail end usually being left behind in the sand.
World Polychaeta Database (WPolyDb)